Long-Term Care Insurance Policy and Development of Elderly Care Enterprises in China - Tianli Yang; Zhong Zhao (Institute of Labor Economics (IZA), 2025)
This paper examines the impact of Long-Term Care Insurance (LTCI) policy on the development of elderly care enterprises in China. Employing a policy shock and a difference-in-differences design, we find that the implementation of LTCI significantly promotes the the number of new entries and survival rate of elderly care enterprises, particularly for individual businesses, enterprises in the health and social work industry, and those located in eastern regions. Notably, service-only LTCI policy exhibits stronger effect on the development of elderly care enterprises compared to policy combining service and cash benefits. Mechanism analysis suggests that LTCI stimulates market demand for formal elderly care services and increases government expenditures on social security and healthcare, both of which drive the development of elderly care enterprises. We also find that LTCI policy boosts labor demand in the elderly care industry. Overall, our empirical findings suggest that LTCI can help address the shortage of long-term care services and enhance family welfare.
Keywords: H55; I28; J14; J26; 330; long-term care insurance; elderly care enterprises; China